Insulin Allergy to Detemir Followed by Rapid Onset of Diabetic Ketoacidosis: A Case Report and Literature Review - Teo, Chong Boon; Tan, Pek Yan; Lee, Shan Xian; Khoo, Joan; Tan, Jun Guan; Ang, Su Fen; Tan, Sze Hwa; Tay, Tunn Lin; Tan, Eberta; Lim, Su Chi; Boehm, Bernhard O.; Loh, Wann Jia (Frontiers in Endocrinology, 2022)
The management of diabetes mellitus in an insulin-dependent patient is challenging in the setting of concomitant antibody-mediated-insulin hypersensitivity. We report a case of a 62-year-old woman with pre-existing type 2 diabetes mellitus of 10 years duration who developed type 3 hypersensitivity reaction to insulin analogue detemir, and subsequently, severe diabetic ketoacidosis (DKA). She was C-peptide negative and was diagnosed with insulin-dependent diabetes. Despite increasing dose requires, insulin-meal matching, and compliance with insulin, she experienced episodes of unexpected hyperglycaemia and hypoglycaemia. The development of rash after detemir initiation and rapid progression to DKA suggests an aberrant immune response leading to the insulin allergy and antibody-induced interference with insulin analogues. Glycaemic control in the patient improved with subcutaneous insulin infusion pump with reduced insulin requirement. However, after a year on pump therapy, localised insulin hypersensitivity reactions started, and glycaemic control gradually deteriorated.